Synthesis & Anticancer Evaluation of New Substituted 2-(3,4-Dimethoxyphenyl)benzazoles - Karaaslan, Cigdem; Duydu, Yalcin; Ustundag, Aylin; Yalcin, Can O.; Kaskatepe, Banu; Goker, Hakan (Medicinal Chemistry, 2019)
Background: The benzazole nucleus is found in many promising small molecules such as anticancer and antibacterial agents. Bendamustine (Alkylating agent), Nocodazole (Mitotic inhibitor), Veliparib (PARP inhibitor), and Glasdegib (SMO inhibitor) are being clinically used as anticancer therapeutic which bear benzimidazole moiety. Based on the principle of bioisosterism, in the present work, 23 compounds belonging to 2-(3,4-dimethoxyphenyl)benzazoles and imidazopyridine series were synthesized and evaluated for their anticancer and antimicrobial activities. Objective: A series of new 2-(3,4-dimethoxyphenyl)-1H-benz(or pyrido)azoles were synthesized and evaluated for their anticancer and antimicrobial activities. Method: N-(5-chloro-2-hdroxyphenyl)-3,4-dimethoxybenzamide 1, was obtained by the amidation of 2-hydroxy-5-chloroaniline with 3,4-dimethoxybenzoic acid by using 1,1'-carbonyldiimidazole. Cyclization of 1 to benzoxazole derivative 2, was achieved by p-toluenesulfonic acid. Other 1H-benz(or pyrido)azoles were prepared by the reaction between 2-aminothiophenol, ophenylenediamine, o-pyridinediamine with sodium metabisulfite adduct of 3,4-dimethoxybenzaldehyde. The NMR assignments of the dimethoxy groups were established by the NOESY spectra. Results: Compound 12, bearing two chlorine atoms at the 5(4) and 7(6) positions of the benzene moiety of benzimidazole was found the most potent analogue against A549 cells with the GI50 value of 1.5 μg/mL. Moreover, 24 showed remarkable cell growth inhibition against MCF-7 and HeLa cells with the GI50 values of 7 and 5.5 μg/mL, respectively. The synthesized compounds have no important antibacterial and antifungal activities. Conclusion: It could be concluded that the introduction of di-chloro atoms at the phenyl ring of 2-(3,4-dimethoxyphenyl)-1H-benzimidazoles increases significant cytotoxicity to selected human tumor cell lines in comparison to other all benzazoles synthesized. Unsubstituted 2-(3,4- dimethoxyphenyl)-imidazopyridines also gave good inhibitory profile against A549 and HeLa cells.
Keywords: 1H-benzimidazole